Khwaja Yusuf Hamadani: Distinguished Mutasawwif Among Sunni = Khwaja Yusuf Hamadani: Mutasawif Tersohor dalam Kalangan Ahli Sunnah - Mansurov, Fatkhiddin; Faudzinaim, Badaruddin (Institut Islam Hadhari, Universiti Kebangsaan Malaysia, 2015)
The Sufi scholar Khwaja Yusuf Hamadani has been largely overlooked by researchers with his life and teachings yet to be subject to in-depth study. Khwaja Yusuf Hamadani studied alongside the prominent and largely celebrated Imam Abu Hamid al-Ghazali with both being taught and receiving their ijazah (licence to teach) by one and the same Murshid. This alone constitutes an undeniable testimony of Khwaja Hamadani’s stature among Sufis. Al-Ghazali differs from Hamadani in that his publications were widely celebrated throughout the Muslim world, whereas Hamadani dedicated most of his lead to teaching his murids, among who are the prominent Ahmad Yasawi and Abdulkhaliq Ghijduwani, who proved influential guides within the Sufi world. One of the most significant contributions of Hamadani in the history of Sufism was his guidance of the founders of the Khwajagan-Naqshbandiyya and Yasawiyya tariqas, which were founded in Central Asia and have since spread throughout the world. This study seeks offers detailed descriptions of Khwaja Yusuf Hamadani in several aspects from which it is hoped that this vibrant personality will become better known outside of Sufi circles.